Global OTC pharmaceutical packaging with a local touch - Kauppinen-Räisänen, Hannele; van der Merwe, Darleen; Bosman, Magdalena (Emerald, 2020)
Purpose - The aim of this study is to explore the contextual influences of packaging design and its cues on respondents' preferences. Design/methodology/approach - To explore the contextuality of packaging cues, a multi-attribute valuation technique, conjoint analysis was used for two types of pharmaceutical products (painkiller and sore throat medicine) across seven countries. Data were collected among respondents (N = 461) from Finland, Ghana, Mongolia, Nigeria, Portuguese, South Africa and the USA. Findings - Similarities and dissimilarities were observed between the product types and countries analysed in terms of the impact of packaging cues. The findings demonstrate the global and local nature of brand cues expressed in retail packaging. Practical implications - The study implies that some cues may serve global markets, while some cues may need to be localised in order to meet the needs of local markets. Understanding these cues and their influences on consumers' brand preferences and choices at the point-of-purchases may enable companies to enter new markets, help them create sustainable and credible global brands. Originality/value - The study contributes to the existing retail packaging literature and pharmaceutical branding literature by providing empirical evidence of the multidimensional aspects of sensory packaging cues. Second, it contributes by showing the contextual nature of retail packaging and its associated cues for OTC pharmaceuticals.
Keywords: brand; colour; global; international; local; retail packaging; consumers; consumer behaviour; brands; marketing; branding; packages; consumption; consumer habits; foodstuffs; multiculturalism; fi=Markkinointi|en=Marketing|